Genetic diversity of Bartonella species in small mammals in the Qaidam Basin, western China - Huaxiang Rao (Nature Portfolio, 2021)
Abstract Investigation of the prevalence and diversity of Bartonella infections in small mammals in the Qaidam Basin, western China, could provide a scientific basis for the control and prevention of Bartonella infections in humans. Accordingly, in this study, small mammals were captured using snap traps in Wulan County and Ge’ermu City, Qaidam Basin, China. Spleen and brain tissues were collected and cultured to isolate Bartonella strains. The suspected positive colonies were detected with polymerase chain reaction amplification and sequencing of gltA, ftsZ, RNA polymerase beta subunit (rpoB) and ribC genes. Among 101 small mammals, 39 were positive for Bartonella, with the infection rate of 38.61%. The infection rate in different tissues (spleens and brains) (χ 2 = 0.112, P = 0.738) and gender (χ 2 = 1.927, P = 0.165) of small mammals did not have statistical difference, but that in different habitats had statistical difference (χ 2 = 10.361, P = 0.016). Through genetic evolution analysis, 40 Bartonella strains were identified (two different Bartonella species were detected in one small mammal), including B. grahamii (30), B. jaculi (3), B. krasnovii (3) and Candidatus B. gerbillinarum (4), which showed rodent-specific characteristics. B. grahamii was the dominant epidemic strain (accounted for 75.0%). Furthermore, phylogenetic analysis showed that B. grahamii in the Qaidam Basin, might be close to the strains isolated from Japan and China. Overall, we observed a high prevalence of Bartonella infection in small mammals in the Qaidam Basin. B. grahamii may cause human disease, and the pathogenicity of the others Bartonella species needs further study, the corresponding prevention and control measures should be taken into consideration.